Have Preferences Become More Similar Worldwide? - Rainer Kotschy; Uwe Sunde (Center for Economic Studies and ifo Institute (CESifo), 2023)
Recent evidence shows substantial heterogeneity in time, risk, and social preferences across and within populations; yet little is known about the dynamics of preference heterogeneity across generations. We apply a novel identification strategy based on dyadic differences in preferences using representative data for 80,000 individuals from 76 countries. Our results document that, among more recent birth cohorts, preferences are more similar across countries and gender gaps in preferences are smaller within countries. This decline in preference heterogeneity across cohorts relates to country-specific differences in preference endowments, population composition, and socioeconomic conditions during formative years, and points at global cultural convergence.
Keywords: D01; J10; J11; 330; patience; willingness to take risks; trust; prosociality; cohort effects